Dissent by design: Fostering student activism in higher education through a case study of student affairs in a public university in the Philippines - Bernardo, M.A.C.; Baranovich, D. (Johns Hopkins University Press, 2016)
Student activism is a ubiquitous component in most democratic societies. Despite its disconcerting implications to the university’s operations, it remains an important agenda to student development in higher education. This study presents the case of a university in the Philippines where student activism is a predominant ethos. The findings expose the role of the wider social context, university, and students in creating a culture of activism. This research uses the case study methodology, initially framed around investigating student affairs practice in a state university in the Philippines, eventually leading to the emergence of student activism as a dominant theme of analysis.